Curable resin composition and adhesive composition

By using bio-curable resin and epoxy resin in the curable resin composition, and using a powder phase dispersion method to disperse the core-shell graft copolymer, the problem of replacing petroleum-based epoxy resin with bio-based epoxy resin is solved. The problem of difficult dispersion is solved, and a curable resin composition with high mechanical properties and environmental protection is achieved.

CN119365535APending Publication Date: 2025-01-24LG CHEM LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480002923.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-01-15
Filing Date
2024-02-01
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively use eco-friendly bio-based epoxy resins to replace petroleum-based epoxy resins, and the powder phase dispersion method has problems of high viscosity and difficulty in dispersing the graft copolymers.

Method used

The cured resin composition containing biochemical resin and epoxy resin is used, and the nuclear-shell-type branches are scattered in cured resin through powder dispersion method to adjust the proportion of biochemical resin to epoxy resin The granularity distribution of the closure of the closure of the closure to improve the decentralized efficiency and mechanical performance.

Benefits of technology

While satisfying the characteristics of mechanical strength, the use of ecological friendly biological base ring oxygen resin reduces environmental pollution, and improves productivity and mechanical properties by optimizing the decentralization method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174470700000031
    Figure BDA0005174470700000031
  • Figure BDA0005174470700000071
    Figure BDA0005174470700000071
  • Figure BDA0005174470700000221
    Figure BDA0005174470700000221
Patent Text Reader

Abstract

The present invention relates to: a curable resin composition which reduces environmental pollution by using an eco-friendly bio-based epoxy resin instead of a conventional petroleum-based epoxy resin, and which satisfies all mechanical strength characteristics required by a curable resin composition comprising a conventional petroleum-based epoxy resin; and has excellent productivity and excellent mechanical properties by dispersing the graft copolymer in the curable resin by a powder phase dispersion method; and an adhesive composition comprising the curable resin composition.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0018787 filed on February 13, 2023 in the Korean Intellectual Property Office, the contents of which are incorporated into this specification by reference. Technical Field

[0003] The present invention relates to a curable resin composition and an adhesive composition comprising the curable resin composition as a toughening agent. Background Art

[0004] Curable resins represented by epoxy resins are used in various fields, such as electrical and electronic products, automotive parts and building materials. Recently, with the increasing interest in eco-friendly biomaterials, efforts are being made to apply eco-friendly biomaterials to epoxy resins. If conventional petroleum-based epoxy resins are replaced by eco-friendly bio-based epoxy resins, environmental pollution occurring during the production of petroleum-based raw materials can be reduced.

[0005] At the same time, for the purpose of improving physical properties and processing properties, curable resins such as epoxy resins are used in combination with additives such as inorganic fillers, release agents and rubber fine particles with rubber-like properties, rather than using curable resins alone. Among them, epoxy resins usually show brittleness and need to improve impact resistance and bonding strength. This requirement is not only applicable to conventional petroleum-based epoxy resins, but also to eco-friendly bio-based epoxy resins.

[0006] As a method for improving the impact resistance of epoxy resin, a method of using a graft copolymer containing a rubbery polymer as an impact reinforcing agent is proposed. The graft copolymer has a particle form of a core-shell structure comprising a core containing a rubbery polymer and a shell formed by graft polymerization onto the core.

[0007] Here, in order to use the graft copolymer as an impact reinforcing agent for epoxy resin, the graft copolymer needs to be dispersed in the epoxy resin. As a method of dispersing the graft copolymer in the epoxy resin, there are a liquid dispersion method and a powder phase dispersion method.

[0008] According to the liquid dispersion method, for a latex-state graft copolymer in which the graft copolymer is dispersed in water, the graft copolymer is dispersed in the epoxy resin by a stepwise solvent replacement method of replacing water with a solvent and then replacing the solvent with an epoxy resin. The liquid dispersion method has the advantage of dispersing the graft copolymer in a uniformly distributed matrix of the epoxy resin, but in order to apply the graft copolymer to the epoxy resin as an impact reinforcing agent, there are storage problems in that the graft copolymer needs to be kept in a latex state until it is dispersed, the process cost is high due to the solvent replacement, and there are environmental problems due to the water and solvent discharged respectively during the replacement process of the graft copolymer and the solvent.

[0009] The powder phase dispersion method has the advantage of low process cost, in which the dry powder formed by the agglomeration of the graft copolymer latex, i.e., the powder phase graft copolymer is directly dispersed in the epoxy resin. However, when the graft copolymer powder is introduced into the epoxy resin, the viscosity of the graft copolymer powder becomes very high, and dispersion becomes very difficult or impossible in practice.

[0010] Therefore, efforts are needed to use eco-friendly bio-based epoxy resins to replace conventional petroleum-based epoxy resins while satisfying all the mechanical strength properties required of curable resin compositions containing conventional petroleum-based epoxy resins, and to apply powder phase dispersion methods to improve both the process cost and environmental aspects of applying impact enhancers to curable resin compositions such as epoxy resins.

[0011] [Prior art literature]

[0012] [Patent Document]

[0013] (Patent Document 1) JP 2006-104328 A Summary of the invention

[0014] Technical issues

[0015] The task to be solved by the present invention is to reduce environmental pollution by applying eco-friendly bio-based epoxy resin to replace conventional petroleum-based epoxy resin while satisfying all the mechanical strength properties required of a curable resin composition containing conventional petroleum-based epoxy resin.

[0016] Furthermore, the task to be solved by the present invention is to apply a powder phase dispersion method to improve both process costs and environmental aspects of applying an impact reinforcing agent to a curable resin composition comprising an eco-friendly bio-based epoxy resin.

[0017] That is, in order to solve the tasks mentioned in the background of the present invention, the purpose of the present invention is to provide a curable resin composition, which uses an eco-friendly bio-based epoxy resin instead of a conventional petroleum-based epoxy resin, satisfies all the mechanical strength characteristics required of a curable resin composition containing a conventional petroleum-based epoxy resin, and has excellent productivity and excellent mechanical properties by dispersing a graft copolymer in the curable resin through a powder phase dispersion method.

[0018] Furthermore, an object of the present invention is to provide a structural adhesive composition including an eco-friendly bio-based epoxy resin as a main material while having excellent mechanical strength by applying a curable resin composition as a toughening agent.

[0019] Technical Solution

[0020] In order to achieve the above-mentioned tasks, the present invention provides a curable resin composition and an adhesive composition.

[0021] (1) The present invention provides a curable resin composition, comprising a continuous phase containing a curable resin and a dispersed phase containing a graft copolymer, wherein the curable resin comprises a biocurable resin and an epoxy resin, and the peak area ratio of the biocurable resin to the epoxy resin (biocurable resin:epoxy resin) is 0.60 to 5.60:1, and the peak area ratio is obtained as follows: 0.2 g of a curable resin composition sample is dissolved in acetone, 40 mL of methanol is added thereto, the supernatant is filtered into a 2 mL liquid chromatography vial using a 0.22 μm polytetrafluoroethylene filter, and high performance liquid chromatography (HPLC) is used to detect according to the elution time through an evaporative light scattering detector (ELSD).

[0022] (2) The present invention provides the curable resin composition according to (1), wherein the biocurable resin is a bioepoxy resin.

[0023] (3) The present invention provides the curable resin composition according to (1) or (2), wherein the biocurable resin contains an isosorbide unit.

[0024] (4) The present invention provides the curable resin composition according to any one of (1) to (3), wherein the biocurable resin is represented by the following Formula 1.

[0025] [Formula 1]

[0026]

[0027] In formula 1, R 1 and R 2 Each is independently hydrogen, hydroxyl, epoxy or glycidyl, and n is an integer selected from 1 to 1,000.

[0028] (5) The present invention provides the curable resin composition according to any one of (1) to (4), wherein the epoxy equivalent weight (EEW) of the biocurable resin is 150 g / eq to 190 g / eq.

[0029] (6) The present invention provides the curable resin composition according to any one of (1) to (5), wherein the biocurable resin has a viscosity at 25° C. of 500 to 6,000 cPs.

[0030] (7) The present invention provides a curable resin composition according to any one of (1) to (6), wherein the epoxy resin includes one or more selected from bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin, bisphenol E type epoxy resin, naphthalene type epoxy resin, biphenyl type epoxy resin, dicyclopentadiene type epoxy resin, phenol novolac type epoxy resin, aliphatic cyclic epoxy resin and glycidylamine type epoxy resin.

[0031] (8) The present invention provides the curable resin composition according to any one of (1) to (7), wherein the epoxy equivalent weight (EEW) of the epoxy resin is 180 g / eq to 190 g / eq.

[0032] (9) The present invention provides the curable resin composition according to any one of (1) to (8), wherein the epoxy resin has a viscosity at 25° C. of 8,000 cPs to 13,500 cPs.

[0033] (10) The present invention provides a curable resin composition according to any one of (1) to (9), wherein the curable resin contains 58 wt % to 82 wt % of the biocurable resin and 18 wt % to 42 wt % of the epoxy resin.

[0034] (11) The present invention provides a curable resin composition according to any one of (1) to (10), wherein the graft copolymer is a core-shell type graft copolymer comprising a core containing a rubbery polymer and a shell formed by grafting a graft monomer to the rubbery polymer.

[0035] (12) The present invention provides the curable resin composition according to (11), wherein the rubbery polymer comprises one or more monomer units selected from conjugated diene-based monomer units and alkyl acrylate-based monomer units.

[0036] (13) The present invention provides the curable resin composition according to (11) or (12), wherein the graft monomer includes an alkyl (meth)acrylate monomer.

[0037] (14) The present invention provides a curable resin composition according to any one of (11) to (13), wherein the grafting monomer includes a methyl (meth)acrylate monomer and an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms.

[0038] (15) The present invention provides the curable resin composition according to any one of (11) to (14), wherein the graft monomer further includes an aromatic vinyl-based monomer.

[0039] (16) The present invention provides the curable resin composition according to any one of (11) to (15), wherein the graft copolymer contains 70% to 92% by weight of the core and 8% to 30% by weight of the shell.

[0040] (17) The present invention provides the curable resin composition according to any one of (11) to (16), wherein the average particle diameter of the core is 100 nm to 500 nm.

[0041] (18) The present invention provides the curable resin composition according to any one of (11) to (17), wherein the weight average molecular weight of the shell is 10,000 g / mol to 85,000 g / mol.

[0042] (19) The present invention provides the curable resin composition according to any one of (11) to (18), wherein the average particle size of the graft copolymer is 100 nm to 600 nm.

[0043] (20) The present invention provides an adhesive composition comprising the curable resin composition according to any one of (1) to (19).

[0044] (21) The present invention provides the adhesive composition according to (20), wherein the adhesive composition comprises a main material, a toughening agent, a polyurethane resin and a curing agent, and the toughening agent is the curable resin composition.

[0045] (22) The present invention provides the adhesive composition according to (21), wherein the main material includes a biocurable resin.

[0046] (23) The present invention provides the adhesive composition according to (22), wherein the main material contains the biocurable resin in an amount of 1 wt % to 40 wt % relative to the total content of the adhesive composition.

[0047] (24) The present invention provides an adhesive composition according to any one of (21) to (23), wherein the adhesive composition contains the toughening agent in an amount of 5 wt % to 32 wt % relative to the total content of the adhesive composition.

[0048] Beneficial Effects

[0049] The curable resin composition of the present invention reduces environmental pollution by using eco-friendly bio-based epoxy resin instead of conventional petroleum-based epoxy resin while satisfying all the mechanical strength properties required of a curable resin composition containing conventional petroleum-based epoxy resin, and obtains excellent productivity and excellent mechanical properties by dispersing the graft copolymer in the curable resin through a powder phase dispersion method.

[0050] Furthermore, the adhesive composition of the present invention is a structural adhesive composition and has excellent mechanical strength while including an eco-friendly bio-based epoxy resin as a main material by applying a curable resin composition as a toughening agent. DETAILED DESCRIPTION

[0051] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.

[0052] It should be understood that the words or terms used in the present disclosure and claims should not be understood as the meanings defined in commonly used dictionaries. It will be further understood that based on the inventors can appropriately define the meanings of words or terms to best illustrate the principles of the present invention, the words or terms should be understood to have the same meanings as they are in the technical concept of the present invention.

[0053] The term "monomer unit" used in the present invention may refer to a component, structure or substance itself derived from a monomer, and specifically, may refer to a repeating unit formed in a polymer by the participation of a monomer injected into a polymerization reaction during the polymerization of the polymer.

[0054] As used herein, the term "composition" includes a mixture of materials comprising the composition and reaction products and decomposition products formed from the materials of the composition.

[0055] The present invention provides a curable resin composition.

[0056] According to one embodiment of the present invention, the curable resin composition may include a biocurable resin as a curable resin and a graft copolymer as an impact reinforcing agent. Specifically, the graft copolymer may be dispersed in the curable resin in a powder form.

[0057] According to one embodiment of the present invention, the curable resin composition may include a continuous phase containing a curable resin and a dispersed phase containing a graft copolymer, the curable resin may include a biocurable resin and an epoxy resin, and the peak area ratio of the biocurable resin to the epoxy resin (biocurable resin: epoxy resin) is 0.60 to 5.60:1, and the peak area ratio is obtained as follows: 0.2 g of the curable resin composition sample is dissolved in acetone, 40 mL of methanol is added thereto, the supernatant is filtered into a 2 mL liquid chromatography vial using a 0.22 μm polytetrafluoroethylene filter, and high performance liquid chromatography (HPLC) is used to detect according to the elution time through an evaporative light scattering detector (ELSD).

[0058] According to one embodiment of the present invention, the biocurable resin is an eco-friendly bio-based curable resin, and may be a curable resin prepared from a bio-based material.

[0059] According to one embodiment of the present invention, the biocurable resin may contain derivative units from one or more bio-based materials, and the bio-based materials are selected from plant-derived fatty acid oils, isosorbide, furan derivatives, tannin derivatives, terpene derivatives, rosin derivatives, lignin and lignin derivatives. In a specific embodiment, the derivative units from plant-derived fatty acid oils may be selected from one or more of epoxidized soybean oil units, epoxidized castor oil units, epoxidized linseed oil units, epoxidized canola oil units and epoxidized karanja oil units. In addition, the derivative units from furan derivatives may be selected from one or more of diglycidyl ester units and glycidyl furfuryl ether units of 2,5-furandicarboxylic acid.

[0060] According to one embodiment of the present invention, biocurable resin can specifically comprise isosorbide unit.Isosorbide that forms isosorbide unit is the derivative from sorbitol, and corresponds to the bio-based material that can be produced at low price.Specifically, isosorbide can be obtained by the dehydration of sorbitan.Sorbitan can be obtained by the dehydration of sorbitol, and sorbitol can be obtained by the dehydrogenation of glucose, and glucose can be obtained by the depolymerization of polysaccharide such as cellulose and starch.

[0061] According to one embodiment of the present invention, the biocurable resin may be a bioepoxy resin comprising isosorbide units. In a specific embodiment, the biocurable resin may be a copolymer comprising isosorbide units and epoxy units, and may be more specifically represented by Formula 1 below.

[0062] [Formula 1]

[0063]

[0064] In formula 1, R 1 and R 2 Each of them may be independently hydrogen, hydroxyl, epoxy or glycidyl, and n may be an integer selected from 1 to 1,000. In a specific embodiment, n may be 1 or more, 5 or more, or 10 or more, and 1,000 or less, 900 or less, 800 or less, 700 or less, 600 or less, 500 or less, 400 or less, 300 or less, 200 or less, or 100 or less. In addition, the wavy bonding line is intended to represent hydrogen, oxygen, R 1 and R 2 The three-dimensional structure of and can correspond to both the solid wedge and the dashed wedge. In a specific embodiment, the two hydrogens and oxygens and R 2 The wavy bond wires shown in can have the same orientation, that is, all wavy bond wires can be solid wedges or dashed wedges, R 1 The wavy bond lines shown in the figure can represent the bonding between the two hydrogens and oxygen and R 2 Opposite stereo orientation.

[0065] According to one embodiment of the present invention, the epoxide equivalent weight (EEW) of the biocurable resin may be 150 g / eq to 190 g / eq. In a specific embodiment, the epoxide equivalent weight of the biocurable resin may be 150 g / eq or more, 155 g / eq or more, 160 g / eq or more, or 165 g / eq or more, and 190 g / eq or less, 185 g / eq or less, 180 g / eq or less, 175 g / eq or less, or 170 g / eq or less, and within this range, the effect as a heterogeneous adhesive, specifically as a structural adhesive, may be exhibited.

[0066] According to one embodiment of the present invention, the 25°C viscosity of the biocurable resin may be 500 cPs to 6,000 cPs. In a specific embodiment, the 25°C viscosity of the biocurable resin may be 500 cPs or more, 1,000 cPs or more, 1,500 cPs or more, 2,000 cPs or more, 2,500 cPs or more, or 3,000 cPs or more, and 6,000 cPs or less, 5,500 cPs or less, 5,000 cPs or less, 4,500 cPs or less, 4,000 cPs or less, 3,500 cPs or less, 3,000 cPs or less, 2,500 cPs or less, or 2,000 cPs or less, within which range, due to the low viscosity during mixing of the structural adhesive composition, processability may be further improved.

[0067] According to one embodiment of the present invention, in addition to the biocurable resin, the curable resin may further include other types of curable resins different from the biocurable resin. Here, the other types of curable resins may be epoxy resins, and may specifically include at least two epoxy bonds, and more specifically may be selected from bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol AD ​​epoxy resins, bisphenol E epoxy resins, naphthalene epoxy resins, biphenyl epoxy resins, dicyclopentadiene epoxy resins, phenol novolac epoxy resins, aliphatic cyclic epoxy resins, and glycidylamine epoxy resins. One or more.

[0068] According to one embodiment of the present invention, the epoxy resin may have an epoxy equivalent weight (EEW) of 180 to 190 g / eq, and may have a viscosity of 8,000 to 13,500 cPs at 25° C. Within this range, the effect of the structural adhesive may be further improved.

[0069] According to one embodiment of the present invention, the peak area ratio of the biocurable resin to the epoxy resin (biocurable resin: epoxy resin) can be 0.60 to 5.60: 1, wherein the peak area ratio is obtained by dissolving 0.2g of a curable resin composition sample in acetone, adding 40mL of methanol thereto, filtering the supernatant into a 2mL liquid chromatography vial using a 0.22μm polytetrafluoroethylene filter, and detecting according to the elution time using a high performance liquid chromatography (HPLC) by an evaporative light scattering detector (ELSD). The peak area ratio of the biocurable resin to the epoxy resin detected by an evaporative light scattering detector (ELSD) according to the elution time using a high performance liquid chromatography (HPLC) can be determined according to the ratio of the biocurable resin to the epoxy resin present in the curable resin composition. In a specific embodiment, the peak area ratio of the biocurable resin to the epoxy resin of the curable resin composition detected by high performance liquid chromatography (HPLC) by an evaporative light scattering detector (ELSD) according to the elution time (biocurable resin:epoxy resin) may be 0.60 or more, 0.65 or more, 0.70 or more, 0.75 or more, 0.80 or more, 0.85 or more, 0.90 or more, 0.95 or more, 1.00 or more, or 1.05 or more: 1, and 5.60 or less, 5.50 or less, 5.40 or less, 5.30 or less, 5.20 or less, 5.10 or less, 5.00 or less, 4.90 or less, 4.80 or less, 4.70 or less, 4.60 or less, 4.50 or less, or 4.40 or less: 1. As described above, in the case where a biocurable resin and an epoxy resin are mixed and used as a curable resin, if the peak area ratio (biocurable resin:epoxy resin) of the biocurable resin and the epoxy resin detected by an evaporative light scattering detector (ELSD) using high performance liquid chromatography (HPLC) according to the elution time is controlled as described above, environmental pollution can be reduced by using an eco-friendly bio-based epoxy resin instead of a conventional petroleum-based epoxy resin, all the mechanical strength properties required of a curable resin composition containing a conventional petroleum-based epoxy resin can be met, and the viscosity can be easily adjusted to further improve the dispersion efficiency of the graft copolymer in the curable resin, thereby further improving productivity and mechanical properties.

[0070] According to one embodiment of the present invention, curable resin can comprise 58 wt % to 82 wt % of biocurable resin and 18 wt % to 42 wt % of epoxy resin. In a specific embodiment, curable resin can comprise more than 58 wt %, more than 59 wt %, more than 60 wt %, more than 61 wt %, more than 62 wt %, more than 63 wt %, more than 64 wt % or more than 65 wt %, and less than 82 wt %, less than 81 wt % or less than 80 wt % of biocurable resin, and the epoxy resin of the remaining amount. Like this, if biocurable resin is mixed with epoxy resin and used as curable resin, then viscosity can be easily adjusted, and the dispersion efficiency of graft copolymer in curable resin can be further improved.

[0071] According to one embodiment of the present invention, the graft copolymer may include a core-shell type graft copolymer including a core including a rubbery polymer and a shell formed by graft-copolymerizing a graft monomer to the rubbery polymer.

[0072] According to one embodiment of the present invention, in the core-shell graft copolymer, the core may refer to the rubbery polymer component itself that forms the core or core layer of the graft copolymer, and the shell may refer to the polymer component or copolymer component that forms the shell or shell layer as a shell type, which is grafted and polymerized to the rubbery polymer and surrounds the core. That is, the core containing the rubbery polymer may be the rubbery polymer itself, and the shell may refer to the grafted layer formed by grafting the grafted monomer to the rubbery polymer. According to one embodiment of the present invention, the rubbery polymer is a component that provides impact resistance when the graft copolymer composition is used as an impact enhancer, and may include one or more monomer units selected from conjugated diene monomer units and alkyl acrylate monomer units. In a specific embodiment, the rubbery polymer may be a conjugated diene rubbery polymer or an acrylic rubbery polymer. In a more specific embodiment, the conjugated diene rubbery polymer may be one or more selected from the homopolymer of the conjugated diene monomer and the copolymer of the aromatic vinyl monomer-conjugated diene monomer, and the acrylic rubbery polymer may be a homopolymer of the alkyl acrylate monomer.

[0073] According to one embodiment of the present invention, the conjugated diene monomer of the rubbery polymer may be one or more selected from 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, piperylene, 3-butyl-1,3-octadiene, isoprene and 2-phenyl-1,3-butadiene, specifically, 1,3-butadiene.

[0074] According to one embodiment of the present invention, the aromatic vinyl monomer of the rubber-like polymer can be one or more selected from styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 1-vinylnaphthalene, 4-cyclohexylstyrene, 4-(p-methylphenyl)styrene and 1-vinyl-5-hexylnaphthalene, specifically, styrene.

[0075] According to one embodiment of the present invention, the alkyl acrylate monomer of the rubbery polymer may be an alkyl acrylate monomer having 1 to 12 carbon atoms, specifically, one or more selected from methyl acrylate, ethyl acrylate, propyl acrylate and n-butyl acrylate, more specifically, n-butyl acrylate.

[0076] According to one embodiment of the present invention, the shell is a component for improving compatibility and mechanical properties when the graft copolymer composition is used as an impact reinforcing agent, and as described above, the shell may be a graft layer formed by grafting a graft monomer onto a rubbery polymer. In a specific embodiment, the graft monomer grafted onto the rubbery polymer to form the shell may include an alkyl (meth)acrylate monomer.

[0077] According to one embodiment of the present invention, the (meth)acrylic acid alkyl ester monomer in the grafting monomer can be a (meth)acrylic acid alkyl ester monomer of 1 to 12 carbon atoms, specifically, it can be one or more selected from methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate and n-butyl acrylate.

[0078] According to one embodiment of the present invention, the (meth) acrylate alkyl monomer in the graft monomer can be a (meth) acrylate methyl monomer and a (meth) acrylate alkyl monomer of 2 to 12 carbon atoms, in which case the weight average molecular weight of the shell can be further reduced, so that in the process of dispersing the graft copolymer in the curable resin, the swelling of the shell can be minimized and the increase in viscosity can be prevented. In this case, the (meth) acrylate alkyl monomer can include 50% to 99% by weight, 60% to 90% by weight, or 70% to 85% by weight of a (meth) acrylate methyl monomer, and 1% to 50% by weight, 10% to 40% by weight, or 15% to 30% by weight of a (meth) acrylate alkyl monomer of 2 to 12 carbon atoms.

[0079] According to one embodiment of the present invention, in addition to the (meth) alkyl acrylate monomer, the graft monomer may further include a crosslinkable monomer. That is, the graft monomer may include a methyl (meth) acrylate monomer, an alkyl (meth) acrylate monomer of 2 to 12 carbon atoms, and a crosslinkable monomer.

[0080] According to one embodiment of the present invention, the crosslinkable monomer is used to improve the shell forming ability by simultaneous crosslinking while further improving the compatibility and mechanical properties through the shell in the process of forming the shell by the grafted monomer, and can be one or more selected from the following: (meth) acrylic crosslinking monomers, such as ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, allyl (meth)acrylate, trimethylolpropane tri(meth)acrylate and pentaerythritol tetra(meth)acrylate; and vinyl crosslinkable monomers, such as divinylbenzene, divinylnaphthalene and diallyl phthalate, specifically, polyethylene glycol diacrylate or allyl methacrylate.

[0081] According to one embodiment of the present invention, the graft monomer may further include an aromatic vinyl monomer, that is, the graft monomer may include a methyl (meth)acrylate monomer, an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms, and an aromatic vinyl monomer.

[0082] According to one embodiment of the present invention, the aromatic vinyl monomer of the grafting monomer can be one or more selected from styrene, α-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-propylstyrene, 1-vinylnaphthalene, 4-cyclohexylstyrene, 4-(p-methylphenyl)styrene and 1-vinyl-5-hexylnaphthalene, specifically, styrene.

[0083] According to one embodiment of the present invention, if the grafting monomer further includes an aromatic vinyl-based monomer, the content of the aromatic vinyl-based monomer may be 0.1 wt % to 10.0 wt %, 0.5 wt % to 5.0 wt % or 0.8 wt % to 2.0 wt % based on the total amount of the grafting monomer.

[0084] In the curable resin composition according to the present invention, in order to enable dispersion by a powder phase dispersion method, it may be important to control the content of the core in the graft copolymer and the particle size distribution of the core.

[0085] According to one embodiment of the present invention, the graft copolymer may include 70% to 92% by weight of the core. In a specific embodiment, the graft copolymer may include more than 70% by weight, more than 71% by weight, more than 72% by weight, more than 73% by weight, more than 74% by weight or more than 75% by weight, and less than 92% by weight, less than 91% by weight, less than 90% by weight, less than 89% by weight, less than 88% by weight, less than 87% by weight, less than 86% by weight, less than 85% by weight, less than 84% by weight, less than 83% by weight, less than 82% by weight, less than 81% by weight or less than 80% by weight of the core. Therefore, the graft copolymer can include more than 8 weight %, more than 9 weight %, more than 10 weight %, more than 11 weight %, more than 12 weight %, more than 13 weight %, more than 14 weight %, more than 15 weight %, more than 16 weight %, more than 17 weight %, more than 18 weight %, more than 19 weight % or more than 20 weight %, and less than 30 weight %, less than 29 weight %, less than 28 weight %, less than 27 weight %, less than 26 weight % or less than 25 weight % shell. Within this range, if the graft copolymer composition is dispersed in the curable resin, the increase in viscosity can be prevented by minimizing the swelling of the shell while ensuring sufficient compatibility between the curable resin and the graft copolymer composition. The content of core and shell can be obtained by the content ratio of the rubbery polymer added in the process of preparing the graft copolymer to the graft monomer.

[0086] According to one embodiment of the present invention, the average particle diameter of the core can be 100nm to 500nm, specifically, the average particle diameter can be more than 100nm, more than 150nm, more than 200nm, more than 250nm, more than 260nm, more than 270nm, more than 280nm, more than 290nm or more than 300nm, and less than 500nm, less than 490nm, less than 480nm, less than 470nm, less than 460nm, less than 450nm, less than 440nm, less than 430nm, less than 420nm, less than 410nm, less than 400nm, less than 390nm, less than 380nm, less than 370nm, less than 360nm, less than 350nm, less than 340nm, less than 335nm, less than 330nm or less than 325nm. Within this range, the coagulation between small particles in the process of dispersing the graft copolymer composition in the curable resin can be prevented, and the dispersibility reduction caused by the increase in viscosity can be prevented.

[0087] As described above, by controlling the content of the core and the particle size distribution of the core in the plurality of graft copolymers having cores of different particle sizes included in the graft copolymer composition according to the present invention, dispersion in the curable resin composition can be performed by a powder phase dispersion method.

[0088] According to one embodiment of the present invention, the weight average molecular weight of the shell may be 10,000 g / mol to 85,000 g / mol. In a specific embodiment, the weight average molecular weight of the shell can be 10,000 g / mol or more, 15,000 g / mol or more, 20,000 g / mol or more, 25,000 g / mol or more, 30,000 g / mol or more, 35,000 g / mol or more, or 40,000 g / mol or more, and 85,000 g / mol or less, 84,000 g / mol or less, 83,000 g / mol or less, 82,000 g / mol or less, 81,000 g / mol or less, 80,000 g / mol or less, 75,000 g / mol or less, 70,000 g / mol or less, 65,000 g / mol or less, 60,000 g / mol or less, 55,000 g / mol or less, 50,000 g / mol or less, 45,000 g / mol or less, or 40,000 g / mol or less. Within this range, sufficient compatibility between the curable resin and the graft copolymer can be ensured during the dispersion of the graft copolymer in the curable resin, while minimizing the swelling of the shell to prevent viscosity increase. The weight average molecular weight of the shell can be adjusted by controlling the amount of an initiator, an activator, etc. added during the graft polymerization of the graft monomer in the presence of the rubbery polymer.

[0089] According to one embodiment of the present invention, the average particle size of the graft copolymer can be 100nm to 600nm, specifically, the average particle size can be 100nm or more, 150nm or more, 200nm or more, 250nm or more, 260nm or more, 270nm or more, 280nm or more, 290nm or more, 300nm or more, 305nm or more, 310nm or more, 315nm or more, 320nm or more or 325nm or more, and 600nm or less, 590nm or less, 580nm or less, 570nm or less, 560nm or less In some embodiments, the graft copolymer has a molecular weight of 100 nm or less, and the molecular weight of the graft copolymer can be 100 nm or less. In some embodiments, the graft copolymer has a molecular weight of 100 nm or less, and the molecular weight of the graft copolymer can be 100 nm or less. In some embodiments, the graft copolymer has a molecular weight of 100 nm or less, and the molecular weight of the graft copolymer can be 100 nm or less. In some embodiments, the graft copolymer has a molecular weight of 100 nm or less, and the molecular weight of the graft copolymer can be 100 nm or less. In some embodiments, the graft copolymer has a molecular weight of 100 nm or less, and the molecular weight of the graft copolymer can be 100 nm or less. In some embodiments, the graft copolymer has a molecular weight of 100 nm or less, and the molecular weight of the graft copolymer can be 100 nm or less.

[0090] According to one embodiment of the present invention, the curable resin composition may include 50% to 99% by weight of a continuous phase and 1% to 50% by weight of a dispersed phase. In a specific embodiment, the curable resin composition may include more than 50% by weight, more than 51% by weight, more than 52% by weight, more than 53% by weight, more than 54% by weight, or more than 55% by weight, and less than 99% by weight, less than 95% by weight, less than 90% by weight, less than 85% by weight, less than 80% by weight, less than 75% by weight, less than 70% by weight, less than 65% by weight, less than 60% by weight, or less than 55% by weight of a continuous phase. In addition, accordingly, the curable resin composition may contain more than 1 weight %, more than 5 weight %, more than 10 weight %, more than 15 weight %, more than 20 weight %, more than 25 weight %, more than 30 weight %, more than 35 weight %, more than 40 weight % or more than 45 weight %, and less than 50 weight %, less than 49 weight %, less than 48 weight %, less than 47 weight %, less than 46 weight % or less than 45 weight % of the dispersed phase.

[0091] Furthermore, the present invention provides a method for preparing a curable resin composition for preparing the curable resin composition.

[0092] According to one embodiment of the present invention, a method for preparing a curable resin composition includes: a step (S10) of preparing a graft copolymer latex containing a graft copolymer; a step (S20) of agglomerating and drying the graft copolymer latex prepared in step (S10) to prepare a graft copolymer powder; and a step (S30) of mixing a curable resin with the graft copolymer powder prepared in step (S20) to prepare a curable resin composition, wherein step (S30) is performed by dispersing using a stirrer.

[0093] According to one embodiment of the present invention, step (S10) can be carried out by comprising the following steps: a step (S1) of preparing a rubbery polymer latex containing a rubbery polymer; and a step (S2) of injecting a grafting monomer and performing graft polymerization in the presence of the rubbery polymer latex to prepare a graft copolymer latex, wherein the graft copolymer latex comprises a graft copolymer composition containing a plurality of core-shell type graft copolymers.

[0094] According to one embodiment of the present invention, in the method for preparing a curable resin composition, the type and content of monomers used to perform each step may be the same as those of the above-mentioned curable resin composition.

[0095] According to one embodiment of the present invention, step (S1) is a step of preparing a rubbery polymer for forming a core or a core layer in a core-shell type graft copolymer, and step (S2) is a step of forming a shell or a shell layer as a shell type surrounding the core by graft polymerization to the rubbery polymer.

[0096] According to one embodiment of the present invention, each of step (S1) and step (S2) can be performed by emulsion polymerization, and can be performed in the presence of an emulsifier and an initiator injected during the emulsion polymerization, as well as an electrolyte, a molecular weight regulator, an activator, etc. In this case, when performing step (S1), the particle size distribution of the rubber-like polymer particles can be adjusted by the content of the added emulsifier.

[0097] According to one embodiment of the present invention, the emulsifier may be one or more selected from fatty acid-based emulsifiers and rosin acid-based emulsifiers, and in this case, an excellent effect of latex stability may be obtained.

[0098] According to one embodiment of the present invention, based on 100 parts by weight of the monomer for rubbery polymer polymerization, the amount of the emulsifier added in step (S1) can be 0.1 parts by weight to 3.4 parts by weight, 1.0 parts by weight to 3.3 parts by weight, 1.5 parts by weight to 3.2 parts by weight, 2.0 parts by weight to 3.2 parts by weight, or 2.1 parts by weight to 3.1 parts by weight.

[0099] According to one embodiment of the present invention, based on a total of 100 parts by weight of the rubbery polymer and the monomer used for graft copolymer polymerization, the amount of the emulsifier added in step (S2) can be 0.1 to 1.0 parts by weight, 0.1 to 0.5 parts by weight, or 0.1 to 0.3 parts by weight, and within this range, an excellent latex stability effect can be obtained.

[0100] According to one embodiment of the present invention, step (S1) can be carried out using a water-soluble initiator that can be used in the process of emulsion polymerization, and the water-soluble initiator can include potassium persulfate, sodium persulfate, ammonium persulfate, etc. Step (S2) can be carried out by free radical polymerization using peroxide, redox or azo initiator that can be used in the process of emulsion polymerization, and the redox initiator can be, for example, selected from one or more of tert-butyl hydroperoxide, diisopropylbenzene hydroperoxide and isopropylbenzene hydroperoxide. In this case, the effect of providing a stable polymerization environment can be obtained. If a redox initiator is used, ferrous sulfide, sodium ethylenediaminetetraacetate or sodium formaldehyde sulfoxylate can be further included as an activator redox catalyst.

[0101] According to one embodiment of the present invention, step (S2) can be performed by continuously adding the grafting monomer. When performing step (S2), if the grafting monomer is added in batches before initiating the graft polymerization reaction, the defect of increasing the weight average molecular weight of the shell may occur.

[0102] According to one embodiment of the present invention, the emulsion polymerization in step (S1) and step (S2) may be performed in an aqueous solvent, and the aqueous solvent may be ion-exchanged water.

[0103] According to one embodiment of the present invention, step (S20) is a step for obtaining the graft copolymer prepared in step (S10) as a powder phase, and can be performed by coagulating and drying the graft copolymer latex prepared in step (S10).

[0104] According to one embodiment of the present invention, the coagulation in step (S20) can be carried out by adding a coagulant to the graft copolymer latex. In addition, the coagulation in step (S20) can be carried out by acid coagulation such as aqueous sulfuric acid solution and alkali coagulation such as sodium sulfate, and both acid coagulation and alkali coagulation can be carried out as required. In this case, acid coagulation and alkali coagulation can be carried out simultaneously or step by step. If coagulation is carried out step by step, acid coagulation can be carried out first, and then alkali coagulation can be carried out, or alkali coagulation can be carried out first, and then acid coagulation can be carried out. In addition, as required, the coagulation in step (S20) can be carried out in the presence of an organic dispersant.

[0105] According to one embodiment of the present invention, the drying in step (S20) may be performed by a conventional drying method, and may further include a step of dehydrating the coagulated graft copolymer latex before drying, as required.

[0106] According to one embodiment of the present invention, step (S30) is a step of mixing the curable resin with the graft copolymer by the above-mentioned powder phase dispersion method when the graft copolymer is applied to the curable resin as an impact reinforcing agent, and can be performed by adding the graft copolymer powder to the curable resin and mixing. As described above, the graft copolymer according to the present invention has excellent powder dispersibility and can be directly dispersed in the curable resin in the form of powder. In a specific embodiment, the viscosity of the curable resin composition prepared in step (S30) at 25°C can be 2,000 Pa.s or less, 1,900 Pa.s or less, 1,800 Pa.s or less, 1,700 Pa.s or less, 1,600 Pa.s or less, 1,500 Pa.s or less, 1,450 Pa.s or less, 1,400 Pa.s or less, 1,350 Pa.s or less, or 1,300 Pa.s or less, and 100 Pa.s or more, 200 Pa.s or more, 300 Pa.s or more, 400 Pa.s or more, 500 Pa.s or more, 600 Pa.s or more, 700 Pa.s or more, 800 Pa.s or more, 900 Pa.s or more, 1,000 Pa.s or more, 1,100 Pa.s or more, or 1,200 Pa.s or more, and within this range, the graft copolymer powder has low viscosity and excellent dispersibility.

[0107] In addition, the present invention provides an adhesive composition comprising a curable resin composition. The adhesive composition may be a structural adhesive composition, and may comprise the curable resin composition as a toughening agent.

[0108] According to one embodiment of the present invention, the adhesive composition may include, in addition to the toughening agent, a main material that may be used in an adhesive, a polyurethane resin, and a curing agent, and may further include a curing accelerator and a filler.

[0109] According to one embodiment of the present invention, the main material may include a biocurable resin, as in the curable resin composition. In this case, the type of the biocurable resin may be the same as that of the biocurable resin of the curable resin composition.

[0110] According to one embodiment of the present invention, based on the total content of the adhesive composition, the main material can include the biocurable resin in an amount of 1% to 40% by weight. In a specific embodiment, based on the total content of the adhesive composition, the main material can include the biocurable resin in an amount of more than 1%, more than 5%, more than 10%, more than 15%, or more than 20%, and less than 40%, less than 35%, or less than 30% by weight, and within this range, the effect of the structural adhesive can be further improved.

[0111] According to one embodiment of the present invention, based on the total content of adhesive composition, adhesive composition can include toughener with the content of 5 weight % to 32 weight %.In a specific embodiment, based on the total content of adhesive composition, adhesive composition can include more than 5 weight %, more than 6 weight %, more than 7 weight %, more than 8 weight %, more than 9 weight % or more than 10 weight %, and below 32 weight %, below 31 weight %, below 30 weight %, below 29 weight %, below 28 weight %, below 27 weight %, below 26 weight %, below 25 weight %, below 24 weight %, below 23 weight %, below 22 weight %, below 21 weight %, below 20 weight %, below 19 weight %, below 18 weight %, below 17 weight %, below 16 weight % or below 15 weight % toughener.Within the scope, adhesive, particularly the impact strength of structural adhesive composition relative to heterogeneous adhesive can be further improved.

[0112] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art to which the present invention pertains can easily carry out. However, the present invention can be implemented in various different forms and is not limited to the embodiments described in this specification.

[0113] Examples and Comparative Examples

[0114] Example 1

[0115] <Preparation of Rubber-like Polymer Latex>

[0116] Based on a total of 100 parts by weight of 1,3-butadiene, 75 parts by weight of ion exchange water, 60 parts by weight of 1,3-butadiene, 1.4 parts by weight of potassium rosinate, 0.6 parts by weight of potassium oleate, 0.9 parts by weight of potassium carbonate (K2CO3), 0.3 parts by weight of tert-dodecyl mercaptan and 0.3 parts by weight of potassium persulfate (K2S2O3) were added in batches to a polymerization reactor (autoclave) replaced with nitrogen, and polymerization was carried out at a reaction temperature of 70°C. Then, at a point where the polymerization conversion rate was 30% to 40%, 0.7 parts by weight of potassium oleate was added in batches, 20 parts by weight of 1,3-butadiene was added in batches, and polymerization was continuously carried out at a reaction temperature of 70°C. Then, after the polymerization conversion rate reached 60%, 20 parts by weight of 1,3-butadiene was added in batches, the reaction temperature was raised to 80°C, the polymerization reaction was continuously carried out, and the reaction was terminated at a point where the polymerization conversion rate reached 95%. The total time consumed for the polymerization was 23 hours, and the gel content of the obtained rubbery polymer latex was 76%, and the average particle size of the rubbery polymer particles was 300 nm.

[0117] In this case, the polymerization conversion rate is calculated as the ratio of the weight of the solid content of the obtained rubbery polymer to the weight of the solid content of the charged monomer.

[0118] <Preparation of Graft Copolymer Latex>

[0119] Into a nitrogen-substituted closed polymerization reactor, 75 parts by weight of the rubbery polymer latex thus prepared based on solid content was added, based on a total of 100 parts by weight of the rubbery polymer latex (based on solid content), methyl methacrylate, n-butyl acrylate and styrene, and 200 parts by weight of ion-exchanged water, 0.2 parts by weight of potassium oleate, 0.036 parts by weight of ferrous sulfide, 0.2 parts by weight of sodium ethylenediaminetetraacetate, 0.2 parts by weight of sodium formaldehyde sulfoxylate and 0.25 parts by weight of tert-butyl hydroperoxide were added in batches. Then, polymerization was carried out at a reaction temperature of 60° C. for 4 hours, while 18 parts by weight of methyl methacrylate, 5 parts by weight of n-butyl acrylate and 2 parts by weight of styrene were continuously added over 3 hours to prepare a graft copolymer latex.

[0120] <Preparation of Graft Copolymer Powder>

[0121] The graft copolymer latex thus prepared was diluted in distilled water to 15 wt% based on solid content and put into a coagulation bath, and then the internal temperature of the coagulation bath was raised to 45° C. Thereafter, IR1076 was added as an antioxidant to 100 parts by weight of the graft copolymer based on solid content, stirred while adding an aqueous sulfuric acid solution to coagulate, and the graft copolymer and water were separated, followed by dehydration and drying to prepare a graft copolymer powder.

[0122] <Preparation of Epoxy Resin Composition Dispersed with Graft Copolymer>

[0123] Based on a total of 100 parts by weight of the epoxy resin and the graft copolymer, 55 parts by weight of the epoxy resin and 45 parts by weight of the graft copolymer powder thus prepared were added to a planetary mixer (KMTech, KPLM-0.6) set at 70° C., and stirred at 10 rpm for 1 hour, 80 rpm for 2 hours, and 60 rpm for 10 hours to disperse the graft copolymer powder in the epoxy resin to prepare an epoxy resin composition dispersed with a graft copolymer.

[0124] In this case, 65 wt % of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) and 35 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) were mixed and used as the epoxy resin.

[0125] <Preparation of Structural Adhesive Composition>

[0126] Using a slurry mixer (KM Tech Co., PDM-300), 30 parts by weight of isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) and 25.4 parts by weight of bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) as main materials, 15 parts by weight of the epoxy resin composition prepared above as a toughening agent, 20 parts by weight of a polyurethane resin (Adeka Co., QR-9466), 4.9 parts by weight of a curing agent (Evonik Co., Dicyanex 1400F), 0.7 parts by weight of a curing accelerator (Evonik Co., Amicure UR7 / 10), 3.0 parts by weight of calcium oxide (Youyeong Materials Co., UNI-OX) and 1.0 parts by weight of fumed silica (Carbot Co., CAB-O-SIL In this case, curing agent is added according to the equivalent of epoxy resin, and curing accelerator is added with the equivalent ratio of 1 / 7 of curing agent.

[0127] Example 2

[0128] The epoxy resin composition was prepared in the same manner as in Example 1, except that in the process of preparing the epoxy resin composition in Example 1, 70 wt % of isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) instead of 65 wt % and 30 wt % of bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) instead of 35 wt % were mixed and used as the epoxy resin.

[0129] In addition, in the process of preparing the structural adhesive composition in Example 1, an adhesive composition was prepared in the same manner as in Example 1, except that 40 parts by weight of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 30 parts by weight and 15.4 parts by weight of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the main material, and the same amount of the epoxy resin composition prepared above was added as a toughening agent.

[0130] Example 3

[0131] The epoxy resin composition was prepared in the same manner as in Example 1, except that in the process of preparing the epoxy resin composition in Example 1, 80 wt % of isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) instead of 65 wt % and 20 wt % of bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) instead of 35 wt % were mixed and used as the epoxy resin.

[0132] In addition, in the process of preparing the structural adhesive composition in Example 1, an adhesive composition was prepared in the same manner as in Example 1, except that 20 parts by weight of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 30 parts by weight and 35.4 parts by weight of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the main material, and the same amount of the epoxy resin composition prepared above was added as a toughening agent.

[0133] Example 4

[0134] The epoxy resin composition was prepared in the same manner as in Example 1, except that in the process of preparing the epoxy resin composition in Example 1, 70 wt % of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 65 wt % and 30 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the epoxy resin, 50 parts by weight was added instead of 55 parts by weight of the epoxy resin, and 50 parts by weight was added instead of 45 parts by weight of the prepared graft copolymer powder.

[0135] In addition, the adhesive composition was prepared in the same manner as in Example 1, except that 30.4 parts by weight of bisphenol A epoxy resin (Kukdo Chemical Co., Yd-128) was added as the main material instead of 25.4 parts by weight, and 10 parts by weight of the epoxy resin composition prepared above was added as a toughening agent.

[0136] Example 5

[0137] A rubbery polymer latex was prepared by the same manner as in Example 1, except that 50 parts by weight of ion exchange water was added instead of 75 parts by weight and 1.8 parts by weight of potassium carbonate (K2CO3) was added instead of 0.9 parts by weight during the preparation of the rubbery polymer latex in Example 1.

[0138] In addition, an epoxy resin composition was prepared in the same manner as in Example 1, except that in the process of preparing the epoxy resin composition in Example 1, 70 wt % of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 65 wt % and 30 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the epoxy resin, and an adhesive composition was prepared.

[0139] Example 6

[0140] A graft copolymer latex was prepared by carrying out the same manner as in Example 1, except that 90 parts by weight of the prepared rubbery polymer latex was added instead of 75 parts by weight, 7 parts by weight of methyl methacrylate was added instead of 18 parts by weight, 2 parts by weight of n-butyl acrylate was added instead of 5 parts by weight, and 1 part by weight was added instead of 2 parts by weight of styrene based on the solid content during the preparation of the graft copolymer latex in Example 1.

[0141] In addition, an epoxy resin composition was prepared in the same manner as in Example 1, except that in the process of preparing the epoxy resin composition in Example 1, 70 wt % of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 65 wt % and 30 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the epoxy resin, and an adhesive composition was prepared.

[0142] Example 7

[0143] A graft copolymer latex was prepared in the same manner as in Example 1, except that 0.1 parts by weight of potassium oleate was added instead of 0.2 parts by weight and 0.125 parts by weight of tert-butyl hydroperoxide was added instead of 0.25 parts by weight.

[0144] In addition, an epoxy resin composition was prepared in the same manner as in Example 1, except that in the process of preparing the epoxy resin composition in Example 1, 70 wt % of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 65 wt % and 30 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the epoxy resin, and an adhesive composition was prepared.

[0145] Example 8

[0146] The adhesive composition was prepared in the same manner as in Example 1, except that during the preparation of the structural adhesive composition in Example 1, 25 parts by weight of isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was added instead of 30 parts by weight and 15.4 parts by weight of bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was added instead of 25.4 parts by weight as main materials, and 30 parts by weight of the prepared epoxy resin composition was added as a toughening agent.

[0147] Comparative Example 1

[0148] An epoxy resin composition was prepared in the same manner as in Example 1, except that in the process of preparing the epoxy resin composition in Example 1, 85 wt % of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 65 wt % and 15 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the epoxy resin, and an adhesive composition was prepared.

[0149] Comparative Example 2

[0150] An epoxy resin composition was prepared in the same manner as in Example 1, except that in the process of preparing the epoxy resin composition in Example 1, 50 wt % of an isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was mixed instead of 65 wt % and 50 wt % of a bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the epoxy resin, and an adhesive composition was prepared.

[0151] Comparative Example 3

[0152] An epoxy resin composition was prepared in the same manner as in Example 1, except that in the process of preparing the epoxy resin composition in Example 1, no isosorbide-based epoxy resin (Kukdo Chemical Co., KDBM-1040) was added and only bisphenol A-based epoxy resin (Kukdo Chemical Co., YD-128) was used as the epoxy resin. An adhesive composition was prepared.

[0153] Experimental Example 1

[0154] For the rubbery polymers and graft copolymers prepared in Examples 1 to 8 and Comparative Examples 1 to 3, the average particle diameters of the core and graft copolymers and the weight average molecular weight of the shell were measured and are shown in Tables 1 and 2 below together with the contents of each component.

[0155] *Average particle diameter (nm) of core and graft copolymer: Each of the rubbery polymer latex and graft copolymer latex prepared in Examples 1 to 8 and Comparative Examples 1 to 7 was diluted in distilled water to a concentration of 200 ppm and measured by a dynamic light scattering (DLS) method using NICOMP 380 according to ISO 22412.

[0156] *Weight average molecular weight of shell (g / mol): The weight average molecular weight of the shell in the core-shell type graft copolymer was measured by gel permeation chromatography (GPC, PL GPC220, Agilent Technologies) under the following conditions.

[0157] In this case, a portion of the graft copolymer solution dispersed in tetrahydrofuran was taken and the precipitate was separated by centrifugation. The supernatant was taken, filtered through a 0.45 μm PTFE syringe filter, and used as a sample solution. The graft copolymer standard was 30.0 mg / mL, and the linear polymer was sampled at a concentration of 1.5 mg / mL.

[0158] - Column: PL MiniMixed B x 2

[0159] -Solvent: Tetrahydrofuran (stabilized with BHT)

[0160] -Flow rate: 1.0ml / min

[0161] -Sample concentration: 1.0mg / ml

[0162] -Injection volume: 100μl

[0163] - Column temperature: 30℃

[0164] -Detector: Waters 2414 refractive index detector -Data processing: Empower 3

[0165] [Table 1]

[0166]

[0167] [Table 2]

[0168]

[0169] Experimental Example 2

[0170] For the epoxy resin compositions as curable resin compositions in which the graft copolymers were dispersed prepared in Examples 1 to 8 and Comparative Examples 1 to 3, the dispersion state of the graft copolymers was confirmed by the following method, and the viscosity was measured. The peak area ratios of the biocurable resin to the epoxy resin measured using an evaporative light scattering detector of high performance liquid chromatography were calculated and are shown in Tables 3 and 4 below together with the contents of each component.

[0171] *Dispersion state: The epoxy resin composition was applied to a cold rolled (CR) steel sheet having a size of 25 mm x 100 mm to a thickness of 0.2 mm, and the number of particles observed with the naked eye was confirmed. In this case, if the number of particles observed with the naked eye was less than 10, the dispersion state indicated excellent, if the number was 10 to less than 50, the dispersion state indicated fair, and if the number was 50 or more, the dispersion state indicated poor.

[0172] *25°C viscosity (Pa.S): For the epoxy resin composition prepared above, the 25°C viscosity was measured using a rheometer (Anton paar Co., MRC 302), and the shear rate was shown to be 2.4 s -1 The viscosity value of the next 100s.

[0173] *Peak area ratio: 0.2g of the epoxy resin composition sample prepared above was dissolved in acetone, and 40mL of methanol was added thereto. The supernatant bottle was filtered into a 2mL liquid chromatography vial using a 0.22μm polytetrafluoroethylene (PTFE) filter, and the peak areas of the biocurable resin and epoxy resin were detected by an evaporative light scattering detector (ELSD) according to the elution time using high performance liquid chromatography (HPLC). Then, the peak area ratio of the biocurable resin to the epoxy resin (biocurable resin: epoxy resin) was calculated.

[0174] [Table 3]

[0175]

[0176] [Table 4]

[0177]

[0178] As shown in Table 3, all the curable resin compositions of Examples 1 to 8 prepared according to the present invention all showed excellent dispersion state and 25° C. viscosity of 1,200 to 1,900 Pa.s, and it can be confirmed that the dispersion state is excellent despite being dispersed in the powder phase.

[0179] In contrast, as shown in Table 4, the curable resin composition prepared in Comparative Example 1 was prepared in a non-flowable gel state rather than a flowable liquid of a dispersion, and thus it was confirmed that the graft copolymer was not dispersed in the powder phase.

[0180] Furthermore, the epoxy resin content of the curable resin composition prepared in Comparative Example 2 was increased to the same content as the biocurable resin, and the curable resin composition prepared in Comparative Example 3 did not contain the biocurable resin but contained only the epoxy resin, and therefore, it was confirmed that the dispersibility was reduced.

[0181] Experimental Example 3

[0182] For the structural adhesive compositions prepared in Examples 1 to 8 and Comparative Examples 1 to 3, shear strength and impact peel strength were measured by the following methods, and are shown in Tables 5 and 6 below together with the content of each component.

[0183] * Shear strength (lap shear, MPa): The shear strength of the structural adhesive composition prepared according to ASTM D1002 standard measurement. The size of the specimen is 180mm x 25.4mm x 1.6T (mm), and the size of the side on which the adhesive composition is applied is 25.4mm x 12.5mm. After removing contaminants from one side of the specimen using ethanol, the structural adhesive composition prepared is applied. The thickness of the adhesive composition is kept constant using microbeads, another specimen is covered and fixed thereon, and then cured at 180°C for 30 minutes. After curing, the shear strength is measured by applying a load at a rate of 1.3mm / min using a UTM tester (Instron Co., 5900).

[0184] * Impact peel strength (N / mm): The impact peel strength of the structural adhesive composition prepared above was measured according to ISO 11343 standards. The size of the specimen was 90mm x 20mm x 1.6T (mm), and the size of the side to which the adhesive composition was applied was 30mm x 20mm. After removing contaminants from one side of the specimen using ethanol, the prepared structural adhesive composition was applied. The thickness of the adhesive composition was kept constant using microbeads, another specimen was covered and fixed thereon, and then cured at 180°C for 30 minutes. After curing, it was stabilized at 25°C and -40°C for more than 1 hour, and the impact peel strength according to shear strength was measured by applying a load at a rate of 2mm / sec using an impact strength tester (Instron Co., 9350).

[0185] [Table 5]

[0186]

[0187] [Table 6]

[0188]

[0189] As shown in Table 5, it can be confirmed that all the structural adhesive compositions of Examples 1 to 8 including the curable resin composition prepared according to the present invention as a toughening agent and a biocurable resin as a main material exhibited excellent shear strength and impact peel strength.

[0190] On the contrary, it can be confirmed that in the structural adhesive composition prepared using the curable resin composition of Comparative Example 1, in which an excessive amount of bio-curable resin is used in the curable resin during the preparation of the curable resin composition, the graft copolymer is not dispersed in the curable resin composition, and both the shear strength and the impact peel strength are deteriorated.

[0191] In addition, in the structural adhesive compositions prepared using the curable resin composition prepared in Comparative Example 2 in which the same amount of epoxy resin as the biocurable resin was used in the curable resin and the curable resin composition prepared in Comparative Example 3 in which no curable resin was used but only epoxy resin was used, it was confirmed that the graft copolymer was not dispersed in the curable resin composition and both the shear strength and the impact peel strength were deteriorated.

Claims

1. A curable resin composition comprising a continuous phase containing a curable resin and a dispersed phase containing a graft copolymer, in, The curable resin includes a bio-curable resin and an epoxy resin, The peak area ratio of the biocurable resin to the epoxy resin (biocurable resin: epoxy resin) is 0.60 to 5.60:1, and the peak area ratio is obtained as follows: 0.2 g of the curable resin composition sample is dissolved in acetone, 40 mL of methanol is added thereto, the supernatant is filtered into a 2 mL liquid chromatography vial using a 0.22 μm polytetrafluoroethylene filter, and high performance liquid chromatography (HPLC) is used to detect by an evaporative light scattering detector (ELSD) according to the elution time.

2. The curable resin composition according to claim 1, wherein The biocurable resin is a bioepoxy resin.

3. The curable resin composition according to claim 1, wherein The biocurable resin comprises isosorbide units.

4. The curable resin composition according to claim 1, wherein The biocurable resin is represented by the following formula 1: [Formula 1] In formula 1, R 1 and R 2 are each independently hydrogen, hydroxyl, epoxy or glycidyl, n is an integer selected from 1 to 1,000.

5. The curable resin composition according to claim 1, wherein The biocurable resin has an epoxy equivalent weight (EEW) of 150 g / eq to 190 g / eq.

6. The curable resin composition according to claim 1, wherein The biocurable resin has a viscosity of 500 cPs to 6,000 cPs at 25°C.

7. The curable resin composition according to claim 1, wherein The epoxy resin includes one or more selected from bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol AD ​​epoxy resin, bisphenol E epoxy resin, naphthalene epoxy resin, biphenyl epoxy resin, dicyclopentadiene epoxy resin, phenol novolac epoxy resin, aliphatic cyclic epoxy resin and glycidylamine epoxy resin.

8. The curable resin composition according to claim 1, wherein The epoxy resin has an epoxide equivalent weight (EEW) of 180 g / eq to 190 g / eq.

9. The curable resin composition according to claim 1, wherein The epoxy resin has a viscosity at 25° C. of 8,000 cPs to 13,500 cPs.

10. The curable resin composition according to claim 1, wherein The curable resin comprises 58 wt % to 82 wt % of the biocurable resin and 18 wt % to 42 wt % of the epoxy resin.

11. The curable resin composition according to claim 1, wherein The graft copolymer is a core-shell type graft copolymer including a core containing a rubbery polymer and a shell formed by graft-polymerizing a graft monomer to the rubbery polymer.

12. The curable resin composition according to claim 11, wherein The rubbery polymer includes one or more monomer units selected from conjugated diene-based monomer units and alkyl acrylate-based monomer units.

13. The curable resin composition according to claim 11, wherein The grafting monomer includes an alkyl (meth)acrylate monomer.

14. The curable resin composition according to claim 11, wherein The grafting monomer includes a methyl (meth)acrylate monomer and an alkyl (meth)acrylate monomer having 2 to 12 carbon atoms.

15. The curable resin composition according to claim 11, wherein The grafting monomer further includes an aromatic vinyl monomer.

16. The curable resin composition according to claim 11, wherein The graft copolymer includes 70 to 92 wt % of the core and 8 to 30 wt % of the shell.

17. The curable resin composition according to claim 11, wherein The average particle size of the core is 100 nm to 500 nm.

18. The curable resin composition according to claim 11, wherein The shell has a weight average molecular weight of 10,000 g / mol to 85,000 g / mol.

19. The curable resin composition according to claim 11, wherein The average particle size of the graft copolymer is 100 nm to 600 nm.

20. An adhesive composition comprising the curable resin composition according to any one of claims 1 to 19.

Citation Information

Patent Citations

  • Thermosetting resin composition and its use

    JP2006104328A

  • Variable-depth holographic display device providing expandable eyebox

    KR1020230018787A